Squeezed flow of water-based nanofluid having temperature dependent viscosity and thermal conductivity. (20th April 2021) - Abbasi, F M; Shanakhat, I; Shehzad, S A; Ben Hamida, Mohamed Bechir
Abstract: Subjected to the numerous applications of squeezed flows of nanofluids, this article provides the analysis of squeezed flow of water-based nanofluids. Viscosity and thermal conductivity of nanofluid is considered to vary with temperature. Appropriate modifications in the Brinkman's viscosity and Hamilton-Crosser's thermal conductivity model have been made for the present analysis. Heat generation/absorption has been also considered. Analysis is presented by considering the various nanoparticles (i.e. copper, silver, alumina etc). Physical analysis of numerical results is facilitated via graphs and tables. Comparison for cylindrical and spherical nanoparticles is also provided. Results indicate that the velocity profile shows a decreasing behavior with an increase in squeeze number and decays against incrementing thermal conductivity parameter for both spherical and cylindrical nanoparticles.